Refractory material production process and refractory material prepared by refractory material production process
By adding yttrium oxide and nanozirconia in the melting stage of the refractory material production process, and combining oxygen blown treatment and pretreatment methods, the problem of nanozirconia agglomeration during the casting stage is solved, achieving more uniform dispersion and higher mechanical strength.
Patent Information
- Application Number
- CN202411970464.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
AI Technical Summary
In the existing refractory material production process, nanozirconia is prone to agglomeration when added during the casting stage, affecting its dispersion uniformity in the molten liquid, resulting in performance differences and poor mechanical strength.
By adding yttrium oxide and nanozirconia in the melting stage and combining oxygen blowing treatment, the fluidity of the molten liquid is used to disperse it evenly to avoid agglomeration. At the same time, pretreatment methods such as ultrasonic dispersion and addition of sodium aluminate are used to further improve the dispersion uniformity.
It significantly improves the dispersion uniformity of yttrium oxide and nanozirconia in the melting liquid, reduces performance differences, improves the mechanical strength and consistency of refractory materials, extends service life and reduces maintenance costs.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of refractory materials, and in particular to a refractory material production process and a refractory material prepared therefrom. Background Art
[0002] Refractory materials are a type of inorganic non-metallic materials with a refractoriness of not less than 1580℃. Refractoriness refers to the Celsius temperature at which a cone-shaped specimen of a refractory material can resist high temperature without softening and melting under no load. However, defining refractory materials only by refractoriness is no longer a comprehensive description of refractory materials, and 1580℃ is not absolute. It is now defined as any material whose physical and chemical properties allow it to be used in a high temperature environment is called a refractory material. Refractory materials are widely used in metallurgy, chemical industry, petroleum, machinery manufacturing, silicate, power and other industrial fields. They are used the most in the metallurgical industry, accounting for 50% to 60% of the total output.
[0003] The melting temperature in the refractory production process is generally over 1800°C. During the cooling process of refractory molding, zirconium oxide easily transforms from higher-strength tetragonal zirconia to lower-strength monoclinic zirconia, which has a certain adverse effect on the mechanical strength of the refractory.
[0004] For example, the Chinese patent with application number CN202010996294.3, a refractory material production process and a refractory material prepared therefrom, discloses a refractory material production process and a refractory material prepared therefrom, and relates to the technical field of refractory materials; a refractory material production process, comprising the following steps: S1 mixing: weighing the mixture raw materials, mixing them evenly, and crushing them to obtain a mixture; the mixture raw materials include the following raw materials in parts by weight: 30-35 parts of alumina, 20-30 parts of zircon sand, 8-12 parts of desiliconized zirconium, 0.5-1.5 parts of soda ash, 1-4 parts of calcium silicate, and 0.5-2 parts of ferric oxide; S2 melting: heating the mixture to 1900-2100°C, melting it, passing oxygen for oxygen blowing treatment, and obtaining a casting liquid; S3 casting: taking 0.5-3 parts by weight of yttrium oxide and 1-5 parts by weight of nano zirconium oxide, transferring them into a mold, injecting the casting liquid into the mold, cooling it, and obtaining a refractory material. The production process of refractory materials has the advantage of being easy to improve the mechanical strength of the product. Refractory materials have the advantage of high mechanical strength.
[0005] As a seed crystal, the dispersion uniformity of nano-zirconia in the melt directly affects its effect of inducing the formation of tetragonal zirconia. In the above technical solution, nano-zirconia is added during the casting stage. Since the fluidity of the melt is reduced at this time, it is easy to cause the agglomeration of nano-zirconia, affecting its dispersion uniformity. Summary of the invention
[0006] The embodiments of the present application provide a refractory material production process and a refractory material prepared therefrom, and solve the problem of uneven dispersion that is easily seen in the prior art by optimizing the method of adding yttria and nano-zirconia, thereby reducing the performance differences caused by uneven distribution and improving the mechanical strength of the refractory material.
[0007] The present invention provides a refractory material production process, which specifically includes the following steps: S1 Mixing: weigh the raw materials for the mixture, mix them evenly, and crush them to obtain a mixture; The raw materials of the mixture include the following raw materials in parts by weight: 30-33 parts of aluminum oxide, 20-30 parts of zircon sand, 8-12 parts of desiliconized zirconium, 0.5-1.5 parts of soda ash, 1-4 parts of calcium silicate, and 0.5-2 parts of ferric oxide; S2 melting: heating the mixture to 1900-2100°C, melting for 100-150 minutes, and obtaining a molten liquid; during the melting process, adding 0.5-1.0 parts by weight of yttrium oxide and 1.0-2.0 parts by weight of nano zirconium oxide to the molten liquid, introducing oxygen into the molten liquid for a first oxygen blowing treatment for 8-10 minutes, stopping the oxygen blowing, refining for 15-20 minutes, and then introducing oxygen into the molten liquid for a second oxygen blowing treatment for 8-10 minutes to obtain a casting liquid; S3 casting: take 0.5-2 parts by weight of yttrium oxide and 1.0-3.0 parts by weight of nano zirconium oxide, mix them evenly, transfer them into a mold, inject the casting liquid into the mold, cool it down to no more than 60°C in 7-12 days, and obtain a refractory material.
[0008] Furthermore, the nano zirconium oxide is tetragonal nano zirconium oxide, and the particle size of the tetragonal nano zirconium oxide is 10-100 nm.
[0009] Furthermore, in the S2 melt, oxygen is blown into the molten liquid through an oxygen lance, and the gas outlet end of the oxygen lance is inserted 35-45 cm below the liquid surface of the molten liquid. The oxygen pressure used in the oxygen blowing treatment is 0.38-0.42 MPa, and the oxygen flow rate is 420-480 L / h.
[0010] Furthermore, yttrium oxide and nano zirconium oxide are pretreated before being added.
[0011] Furthermore, the preprocessing is specifically as follows: A1. Mix yttrium oxide and nano zirconium oxide evenly; A2. Using an ultrasonic disperser to perform ultrasonic dispersion treatment on the mixed yttrium oxide and nano-zirconia, sodium aluminate is added during the ultrasonic dispersion process to fully mix the sodium aluminate with the yttrium oxide and nano-zirconia to form a uniform dispersion system; The amount of sodium aluminate added is 3.5%-5% of the total amount of yttrium oxide and nano zirconium oxide, and the ultrasonic dispersion time is 1-2 hours.
[0012] Furthermore, during the melting of S2, the pretreated yttrium oxide and nano zirconium oxide are added to the melt, and the adding position is set at the oxygen blowing position.
[0013] Furthermore, the nano-zirconia added in the S2 melting stage is a combination of large-particle nano-zirconia and small-particle nano-zirconia; the large-particle nano-zirconia is 60-100nm, and the small-particle nano-zirconia is 10-60nm; the dosage ratio of small-particle nano-zirconia to large-particle nano-zirconia is 1:(1.5-2).
[0014] Furthermore, the particle sizes of nano-zirconia added in the S2 melting and S3 casting stages are different.
[0015] Furthermore, large-particle nano-zirconia with a particle size of 60-100 nm is added in the S2 melting stage; small-particle nano-zirconia with a particle size of 10-60 nm is added in the S3 casting stage.
[0016] A refractory material is produced by the refractory material production process.
[0017] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages: First, yttrium oxide and nano-zirconia are added in the melting stage, and the fluidity of the melt is used to make them uniformly dispersed. Combined with oxygen blowing treatment, their uniformity of dispersion in the melt can be significantly improved, and the agglomeration phenomenon caused by addition in the pouring stage is avoided, thereby reducing the performance difference caused by uneven distribution and improving the consistency and reliability of the product; due to the uniform distribution of yttrium oxide and nano-zirconia, they are prompted to better play the role of seed induction, promote the formation of tetragonal zirconia, increase the content of tetragonal zirconia in the refractory, and significantly improve the mechanical strength, thereby extending the service life of the refractory and reducing the replacement frequency and maintenance cost; Secondly, the dispersion uniformity of yttrium oxide and nano-zirconia affects the performance of the final refractory material. Pretreatment can effectively break the agglomeration between the raw material particles through ultrasonic dispersion, thereby improving the dispersion uniformity; sodium aluminate, as a dispersant, can be adsorbed on the surface of yttrium oxide and nano-zirconia particles to form a protective film to prevent the particles from re-agglomerating. At the same time, sodium aluminate can also reduce the surface energy of the particles, making them easier to disperse; through pretreatment, the dispersant can be fully wrapped on the surface of yttrium oxide and nano-zirconia to form a thin dispersant film, which can effectively prevent the agglomeration of yttrium oxide and nano-zirconia; nano-zirconia, as a seed, can induce zirconium dioxide to generate small-particle high-strength tetragonal zirconia during the melting process. Pretreatment allows the nano-zirconia to be evenly dispersed before melting, thereby better exerting its seed induction effect and improving the mechanical strength and refractory performance of the refractory material; Third, the combined use of small-size and large-size zirconia can form a particle size gradient in the melt; this gradient can optimize the filling effect between particles and improve the overall dispersion uniformity in the melt. Small-size particles can fill the gaps between large-size particles, reduce the void ratio, and improve the density of the material; small-size zirconia particles have a higher specific surface area and activity, can more effectively play a seed induction role, and promote the formation of tetragonal zirconia; large-size zirconia particles can stabilize the dispersion system and provide a growth matrix for small-size particles, making the seed induction effect more durable and stable; the combined use of small-size and large-size zirconia makes the dispersion of zirconia particles in the melt more uniform, reduces the occurrence of agglomeration, improves the overall uniformity of the refractory material, and thus improves its performance; uniformly dispersed zirconia particles can form a tighter structure in the refractory material, improve the internal bonding force of the material, reduce the generation of stress concentration points, and improve the mechanical strength of the refractory material; Fourthly, the high temperature environment in the melting stage is conducive to the dispersion and stabilization of large-particle nano-zirconia, while the lower temperature in the pouring stage is suitable for the uniform filling of small-particle nano-zirconia; nano-zirconia of different particle sizes is added at different stages to form a particle size gradient. Large-particle particles form a stable skeleton in the melting stage, and small-particle particles fill the gaps in the pouring stage. This gradient structure can optimize the filling effect between particles and improve the density of the material; small-particle nano-zirconia has a higher specific surface area and activity, can more effectively play a seed induction role, and promote the formation of tetragonal zirconia, while large-particle nano-zirconia can stabilize the dispersion system and provide a growth matrix for small-particle particles. DETAILED DESCRIPTION
[0018] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.
[0019] Embodiment 1: A refractory material production process, specifically comprising the following steps: S1 Mixing: weigh the raw materials for the mixture, mix them evenly, and crush them to obtain a mixture; The raw materials of the mixture include the following raw materials by weight: 30-33 parts of aluminum oxide, 20-30 parts of zircon sand, 8-12 parts of desiliconized zirconium, 0.5-1.5 parts of soda ash, 1-4 parts of calcium silicate, and 0.5-2 parts of ferric oxide; the particle size of the mixture is not more than 700 μm; S2 melting: heating the mixture to 1900-2100°C, melting for 100-150 minutes, and obtaining a molten liquid; during the melting process, adding 0.5-1.0 parts by weight of yttrium oxide and 1.0-2.0 parts by weight of nano zirconium oxide to the molten liquid, introducing oxygen into the molten liquid for a first oxygen blowing treatment for 8-10 minutes, stopping the oxygen blowing, refining for 15-20 minutes, and then introducing oxygen into the molten liquid for a second oxygen blowing treatment for 8-10 minutes to obtain a casting liquid; The nano zirconium oxide is tetragonal nano zirconium oxide, and the particle size of the tetragonal nano zirconium oxide is 10-100 nm; oxygen blowing treatment is carried out by introducing oxygen into the molten liquid through an oxygen gun, and the gas outlet end of the oxygen gun is inserted into the position 35-45 cm below the liquid surface of the molten liquid. The oxygen pressure used in the oxygen blowing treatment is 0.38-0.42 MPa, and the oxygen flow rate is 420-480 L / h; S3 casting: take 0.5-2 parts by weight of yttrium oxide and 1.0-3.0 parts by weight of nano zirconium oxide, mix them evenly, transfer them into a mold, inject the casting liquid into the mold, cool it down to no more than 60°C in 7-12 days, and obtain a refractory material.
[0020] In the experiment for this process, the addition amount of each raw material is specifically 32kg of aluminum oxide, 26.3kg of zircon sand, 10kg of desiliconized zirconium, 1kg of soda ash, 2.5kg of calcium silicate, 1.2kg of ferric oxide, 1.8kg of yttrium oxide, and 3kg of tetragonal nano-zirconia, wherein 0.8kg of yttrium oxide and 1.2kg of tetragonal nano-zirconia are added to the S2 melt, and the remaining yttrium oxide and tetragonal nano-zirconia are added to the S3 casting stage; The comparative example adopts the Chinese patent method with application number CN202010996294.3 to prepare the refractory material. The difference between the comparative example and the present embodiment is that yttrium oxide and nano-zirconia are only added in the S3 pouring stage.
[0021] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: In the melting stage, the melt is at a high temperature and has high fluidity. At this time, yttrium oxide and nano-zirconia are added, which are easier to be evenly dispersed in the melt, avoiding uneven distribution caused by reduced melt fluidity in the casting stage; oxygen blowing treatment not only provides the oxygen atmosphere required for the oxidation fusion method of zirconium corundum, but also enables the melt to flow, further promoting the uniform distribution of yttrium oxide and nano-zirconia. Nano-zirconia has an extremely small particle size and a high specific surface area, making it easier to disperse in the melt; adding in the melting stage, combined with oxygen blowing treatment, nano-zirconia as a seed can induce zirconium dioxide to generate small-particle high-strength tetragonal zirconia during the melting process. Adding nano-zirconia in the melting stage can make it fully dispersed in the melt, better play its seed induction role, and improve the performance of refractory materials; yttrium oxide and nano-zirconia begin to play a role in stabilizing tetragonal zirconia in the melting stage, which can prevent the transformation of tetragonal zirconia to monoclinic phase earlier, thereby maintaining the stability of the material during the entire melting and casting process; Yttrium oxide and nano-zirconia are added in the melting stage, and the fluidity of the melt is utilized to make them evenly dispersed. In combination with oxygen blowing treatment, their dispersion uniformity in the melt can be significantly improved, and agglomeration caused by addition in the pouring stage can be avoided, thereby reducing performance differences caused by uneven distribution and improving product consistency and reliability. Due to the uniform distribution of yttrium oxide and nano-zirconia, they can better play the role of seed induction and promote the formation of tetragonal zirconia. The content of tetragonal zirconia in the refractory material is increased, and the mechanical strength is significantly improved, thereby extending the service life of the refractory material and reducing the replacement frequency and maintenance cost.
[0022] Example 2: The above Example 1 avoids the uneven distribution caused by the reduced fluidity of the molten liquid during the pouring stage by adding yttrium oxide and nano-zirconia during the melting stage and combining it with oxygen blowing treatment, promotes the uniform distribution of yttrium oxide and nano-zirconia, better exerts their seed induction effect, and improves the mechanical strength of the refractory material. In order to further improve the mechanical strength of the refractory material, further improvements are made on the basis of Example 1.
[0023] Yttrium oxide and nano zirconium oxide are pretreated before being added, and the pretreatment is specifically as follows: A1. Mix yttrium oxide and nano zirconium oxide evenly; A2. Using an ultrasonic disperser to perform ultrasonic dispersion treatment on the mixed yttrium oxide and nano-zirconia, sodium aluminate is added during the ultrasonic dispersion process to fully mix the sodium aluminate with the yttrium oxide and nano-zirconia to form a uniform dispersion system; The amount of sodium aluminate added is 3.5%-5% of the total amount of yttrium oxide and nano zirconium oxide, and the ultrasonic dispersion time is 1-2 hours; In S2 melting, the pretreated yttrium oxide and nano zirconium oxide are added into the melt; Among them, the adding position is set at the oxygen blowing position.
[0024] This embodiment is experimented on the basis of the experiment of the first embodiment. The difference between this embodiment and the experiment of the first embodiment is that the yttrium oxide and the nano-zirconia are pretreated in this embodiment, and the yttrium oxide and the nano-zirconia are added at the oxygen blowing position.
[0025] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: The dispersion uniformity of yttrium oxide and nano-zirconia affects the performance of the final refractory material. Pretreatment can effectively break the agglomeration between raw material particles through ultrasonic dispersion, thereby improving the dispersion uniformity; sodium aluminate, as a dispersant, can be adsorbed on the surface of yttrium oxide and nano-zirconia particles to form a protective film to prevent the particles from re-agglomerating. At the same time, sodium aluminate can also reduce the surface energy of the particles, making them easier to disperse; through pretreatment, the dispersant can be fully wrapped on the surface of yttrium oxide and nano-zirconia to form a thin dispersant film, which can effectively prevent the agglomeration of yttrium oxide and nano-zirconia; nano-zirconia, as a seed, can induce zirconium dioxide to generate small-particle high-strength tetragonal zirconia during the melting process. Pretreatment allows nano-zirconia to be evenly dispersed before melting, thereby better exerting its seed induction effect and improving the mechanical strength and refractory performance of the refractory material; The pretreated yttrium oxide and nano zirconium oxide are added to the melt at the oxygen blowing position, and the particles are more evenly dispersed in the melt by utilizing the strong stirring of the melt and the effect of the oxygen flow during oxygen blowing. The oxygen blowing position is an area with strong fluidity and high oxygen concentration in the melt, which is conducive to the dispersion and uniform distribution of the particles. The pretreated particles are added at the oxygen blowing position, which further utilizes the stirring effect of the melt, so that the particles are more evenly dispersed in the melt. The uniform dispersion system can optimize the microstructure of the refractory material, improve its mechanical strength, heat resistance and corrosion resistance. Yttria and nano-zirconia, as seed inducers, can form more fine grains in the melt, thereby enhancing the density and hardness of the refractory material. At the same time, the addition of dispersants can also reduce the pores and cracks in the refractory material and improve its overall performance. The pretreated yttrium oxide and nano-zirconia are added at the oxygen blowing position, so that they are more evenly dispersed in the melt, reducing the performance difference caused by uneven distribution, and improving the consistency and reliability of the product. At the same time, the optimization of the pretreatment and the adding position makes the nano-zirconia more evenly dispersed in the melt, so as to better play its seed induction role and promote the formation of tetragonal zirconia. The seed induction role of nano-zirconia is fully exerted, so that the content of tetragonal zirconia in the refractory material is increased and the mechanical strength is significantly improved. The optimization of the pretreatment process and the adding position provides a basis for the uniform dispersion of yttrium oxide and nano-zirconia in the melt, making the melting and casting process more stable and controllable, optimizing the production process, and improving production efficiency and product quality.
[0026] Example 3: The above Example 2 pretreats yttrium oxide and nano-zirconium oxide, and adds the pretreated yttrium oxide and nano-zirconium oxide into the melt at the oxygen blowing position, so that they are dispersed more evenly in the melt, thereby increasing the content of tetragonal zirconia in the refractory material and significantly improving the mechanical strength. In order to further improve the mechanical strength of the refractory material, further improvements are made on the basis of Example 2.
[0027] The nano-zirconia added in the S2 melting stage is a combination of large-size nano-zirconia and small-size nano-zirconia; The large-particle size of nano zirconium oxide is 60-100 nm, and the small-particle size of nano zirconium oxide is 10-60 nm; the dosage ratio of the small-particle size of nano zirconium oxide to the large-particle size of nano zirconium oxide is 1:(1.5-2).
[0028] This embodiment is experimented on the basis of the experiment of the second embodiment. The difference between this embodiment and the experiment of the second embodiment is that the nano-zirconia added in the melting stage of step S2 in this embodiment is a combination of large-particle-size and small-particle-size nano-zirconium oxide, the large-particle-size nano-zirconium oxide is 60-100nm, and the small-particle-size nano-zirconium oxide is 10-60nm; the usage ratio of small-particle-size nano-zirconium oxide to large-particle-size nano-zirconium oxide is 1:1.8.
[0029] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: The combined use of small-sized and large-sized zirconia can form a particle size gradient in the melt; this gradient can optimize the filling effect between particles and improve the overall dispersion uniformity in the melt. Small-sized particles can fill the gaps between large-sized particles, reduce the void ratio, and improve the density of the material; small-sized zirconia particles have a higher specific surface area and activity, can more effectively play a seed induction role, and promote the formation of tetragonal zirconia; large-sized zirconia particles can stabilize the dispersion system and provide a growth matrix for small-sized particles, making the seed induction effect more durable and stable; the combined use of small-sized and large-sized zirconia makes the dispersion of zirconia particles in the melt more uniform, reduces the occurrence of agglomeration, improves the overall uniformity of the refractory material, and thus improves its performance; uniformly dispersed zirconia particles can form a tighter structure in the refractory material, improve the internal bonding force of the material, reduce the generation of stress concentration points, and improve the mechanical strength of the refractory material; Through the improvement of particle size gradient effect and dispersion uniformity, the density of the material is significantly improved, thereby enhancing the mechanical strength of the material; the particle size combination of small and large particle size zirconia optimizes the microstructure of the refractory material. By forming a particle size gradient, the structure of the refractory material can be made denser and more uniform, thereby improving its corrosion resistance and heat resistance; the use of particle size combination makes the microstructure of the material more uniform and dense, reducing the generation of defects such as pores and cracks; the seed induction effect of small particle size nano zirconia and the stabilizing effect of large particle size nano zirconia on the dispersed system jointly promote the formation of tetragonal zirconia; tetragonal zirconia has higher hardness and toughness, which can improve the performance of refractory materials and at the same time improve the processing performance of refractory materials.
[0030] Example 4: The above Example 3 achieves the improvement of particle size gradient effect and dispersion uniformity by using a combination of small-particle and large-particle zirconia, and the density of the material is significantly improved, thereby enhancing the mechanical strength of the material. In order to further improve the mechanical strength of the refractory material, further improvements are made on the basis of Example 3.
[0031] The particle sizes of nano zirconium oxide added in the S2 melting and S3 casting stages are different. Large-particle nano zirconium oxide with a particle size of 60-100 nm is added in the S2 melting stage; small-particle nano zirconium oxide with a particle size of 10-60 nm is added in the S3 casting stage.
[0032] The present embodiment is experimented on the basis of the experiment of the third embodiment. The difference between the present embodiment and the experiment of the second embodiment is that the particle sizes of the nano-zirconia added in the melting stage S2 and the casting stage S3 are different in the present embodiment. The large-particle nano-zirconia with a particle size of 60-100nm is added in the melting stage S2; the small-particle nano-zirconia with a particle size of 10-60nm is added in the casting stage S3.
[0033] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: The high temperature environment in the melting stage is conducive to the dispersion and stability of large-particle nano-zirconia, while the lower temperature in the pouring stage is suitable for the uniform filling of small-particle nano-zirconia; nano-zirconia of different particle sizes is added at different stages to form a particle size gradient. Large-particle particles form a stable skeleton in the melting stage, and small-particle particles fill the gaps in the pouring stage. This gradient structure can optimize the filling effect between particles and improve the density of the material; small-particle nano-zirconia has a higher specific surface area and activity, can more effectively play a seed induction role, and promote the formation of tetragonal zirconia, while large-particle nano-zirconia can stabilize the dispersion system and provide a growth matrix for small-particle particles. The large-size particles in the melting stage form a stable dispersion system, and the small-size particles in the pouring stage fill the gaps, thereby improving the overall uniformity of the material; the addition of nano-zirconia of different particle sizes at different stages forms a more obvious particle size gradient effect, thereby further optimizing the filling effect between particles, improving the dispersion uniformity of zirconia particles in the refractory material, and thus enhancing the mechanical strength of the material; the combination of phased addition and particle size gradient significantly improves the mechanical strength of the refractory material; large-size nano-zirconia stabilizes the dispersion system, and small-size nano-zirconia plays a seed induction role, promoting the formation of tetragonal zirconia and improving the hardness and toughness of the material; the existence of the particle size gradient makes the structure of the refractory material more compact and uniform, reduces the generation of defects such as pores and cracks, and improves the overall performance and service life of the material.
[0034] Performance Testing The refractory products are cut into several standard test pieces with the size of 230mm*114mm*65mm for compressive strength and flexural strength tests.
[0035] 1. Compressive strength: Refer to GB / T5072.2-2004 "Test method for compressive strength of refractory materials at room temperature" published method 3: Test method for compressive strength of insulating refractory materials, conduct compressive strength test, and calculate the compressive strength of different products at room temperature; Sample No. Room temperature compressive strength (MPa) Room temperature flexural strength (MPa) Comparative Example 32.4 7.6 Embodiment 1 34.02 8.05 Embodiment 2 35.04 8.37 Embodiment 3 35.76 8.63 Embodiment 4 36.82 8.91 The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A refractory material production process, characterized in that: The specific steps include: S1 Mixing: weighing the raw materials for the mixture, mixing them evenly, and crushing them to obtain a mixture; The raw materials of the mixture include the following raw materials in parts by weight: 30-33 parts of aluminum oxide, 20-30 parts of zircon sand, 8-12 parts of desiliconized zirconium, 0.5-1.5 parts of soda ash, 1-4 parts of calcium silicate, and 0.5-2 parts of ferric oxide; S2 melting: heating the mixture to 1900-2100°C, melting for 100-150 minutes to obtain a molten liquid; During the melting process, 0.5-1.0 parts by weight of yttrium oxide and 1.0-2.0 parts by weight of nano zirconium oxide are added to the melt, oxygen is introduced into the melt for a first oxygen blowing treatment for 8-10 minutes, oxygen blowing is stopped, refining is performed for 15-20 minutes, and oxygen is introduced into the melt for a second oxygen blowing treatment for 8-10 minutes to obtain a casting liquid; S3 casting: take 0.5-2 parts by weight of yttrium oxide and 1.0-3.0 parts by weight of nano zirconium oxide, mix them evenly, transfer them into a mold, inject the casting liquid into the mold, cool it down to no more than 60°C in 7-12 days, and obtain a refractory material.
2. The refractory material production process according to claim 1, characterized in that: The nano zirconium oxide is tetragonal nano zirconium oxide, and the particle size of the tetragonal nano zirconium oxide is 10-100nm.
3. The refractory material production process according to claim 1, characterized in that: S2 Oxygen blowing treatment during melting: oxygen is introduced into the molten liquid through an oxygen lance, and the gas outlet end of the oxygen lance is inserted 35-45cm below the liquid surface of the molten liquid. The oxygen pressure used in the oxygen blowing treatment is 0.38-0.42MPa, and the oxygen flow rate is 420-480L / h.
4. The refractory material production process according to claim 3, characterized in that: Yttria and nano-zirconia are pretreated before being added.
5. The refractory material production process according to claim 4, characterized in that: The preprocessing is specifically as follows: A1. Mix yttrium oxide and nano zirconium oxide evenly; A2. Using an ultrasonic disperser to perform ultrasonic dispersion treatment on the mixed yttrium oxide and nano-zirconia, sodium aluminate is added during the ultrasonic dispersion process to fully mix the sodium aluminate with the yttrium oxide and nano-zirconia to form a uniform dispersion system; The amount of sodium aluminate added is 3.5%-5% of the total amount of yttrium oxide and nano zirconium oxide, and the ultrasonic dispersion time is 1-2 hours.
6. The refractory material production process according to claim 5, characterized in that: During the S2 melting, the pretreated yttrium oxide and nano zirconium oxide are added into the melt, and the adding position is set at the oxygen blowing position.
7. The refractory material production process according to claim 6, characterized in that: The nano zirconium oxide added in the S2 melting stage is a combination of large-particle nano zirconium oxide and small-particle nano zirconium oxide; the large-particle nano zirconium oxide is 60-100nm, and the small-particle nano zirconium oxide is 10-60nm; the dosage ratio of small-particle nano zirconium oxide to large-particle nano zirconium oxide is 1:(1.5-2).
8. The refractory material production process according to claim 6, characterized in that: The particle sizes of nano-zirconia added in the S2 melting and S3 pouring stages are different.
9. The refractory material production process according to claim 8, characterized in that: In the S2 melting stage, large-particle nano-zirconia with a particle size of 60-100 nm is added; in the S3 casting stage, small-particle nano-zirconia with a particle size of 10-60 nm is added.
10. A refractory material, characterized in that: The refractory material is produced by the refractory material production process described in any one of claims 1 to 9.
Citation Information
Patent Citations
Production process for refractory material and refractory material prepared by using same
CN112110716A
Zirconia toughening of glass-ceramic materials
EP0255023A1
Zirconia sintered body and production method thereof
JP2015196624A
Zirconia refractory materials for superhigh temperature using nano-powder
KR1020160136766A
Ceramic reflector of high quality and low cost for crystal growth of oxides and manufacturing method thereof
KR1020180037382A